PERCENTAGE OF ELIGIBILITY OF GOAT LIVERS FROM OLDER ANIMALS SLAUGHTERED AND DISTRIBUTED TO THE COMMUNITY DURING EID AL-ADHA 2025 THROUGH POST-MORTEM EXAMINATION IN EAST DENPASAR DISTRICT, DENPASAR CITY - I Komang Sada Wiratama; I Made Damriyasa; Romy Muhammad Dary Mufa (Buletin Veteriner Udayana, 2025)
Eid al-Adha is closely associated with large-scale animal slaughter, making it essential to ensure the safety of meat and organs distributed to the community. The liver is one of the vital organs shared with consumers but is prone to abnormalities, particularly in older goats. This study aimed to determine the percentage of suitability of goat livers (Capra spp.) from older sacrificial animals through post-mortem examination in East Denpasar District in 2025. A descriptive observational design with a cross-sectional approach was employed. A total of 42 goat liver samples were collected from five villages using purposive sampling combined with cluster sampling. Post-mortem examinations were performed through inspection, palpation, and incision, assessing parameters of shape, color, consistency, and odor. The results revealed that 39 samples (92.8%) were normal and deemed suitable for consumption, while 3 samples (7.2%) exhibited abnormalities such as white spots and pale discoloration, making them conditionally consumable after the removal of unfit portions. No samples were completely rejected or required special heat treatment. In conclusion, most livers of older sacrificial goats in the study area still met the Safe, Healthy, Wholesome, and Halal standards. Post-mortem inspection proved to be an essential preventive measure to safeguard food safety from sacrificial animals. It is recommended that similar inspections be consistently implemented to prevent unsuitable organs from being distributed to the public.